PENGATURAN TINDAK PIDANA PORNOGRAFI DALAM SISTEM HUKUM INDONESIA - Martini, Martini (Faculty of Law, University of Palembang, 2021)
The regulation of pornography in the legal system in Indonesia begins with regulating criminal acts, followed by criminal acts of pornography, and ends with the essence of regulating pornography crimes. The criminal act of pornography in the Indonesian criminal law system, among others, is regulated in the Criminal Code (KUHP) as a crime against decency as regulated in Article 281 and Article 282. In particular, pornography is regulated in the Pornography Law Number 44 of 2008 which regulates about pornography which is a criminal act. Law Number 19 Year 2016 Amendments to Law Number 11 Year 2008 Concerning Information and Transactions (UU ITE), particularly in the use of the internet, alludes to the issue of pornography but is related to content that violates decency. There are sanctions against pornography, both the main and additional crimes in accordance with the applicable provisions